Pembelajaran Bahasa Inggris untuk Bisnis melalui E-Learning - Rina Patriana Chairiyani (Bina Nusantara University, 2013)
The objective of this research is to understand comprehensively the learning process of English for business through e-learning. The research was a qualitative research with an ethnography method conducted in Bina Nusantara University, Jakarta in 2012. The data were collected through observation, interview, document study, and recording. The focus of this research is learning business English by e-learning with sub-focus the process of learning English for business through e-learning. The results obtained from this study are based on the focus of the study: the process of learning English through e-learning. English language learning via e-learning in Binus online uses e-learning system that is asynchronous, which means do not coincide. Both lecturers and students access not at the same time; lodging Binus Online, timing set, so that everything goes according to schedule. The process of teaching and learning through e-learning course is different from the conventional classroom. This process requires both lecturers and students to play an active role and really should take the time for it. Based on the findings of research on learning English for business through e-learning at Binus Online, it can be concluded that the learning process goes well and effective in improving student competence and achievement. The learning process is also a result of good support for students and faculty as well as the adequate support given means of learning English for business done through e-learning at Binus Online. In addition, learning through e-learning has a direct impact with the emergence of spirit of the students to always work hard, on time, independent, and active.